ANALISIS KONFIGURASI APRON TAXIWAY TERHADAP BEBAN KERJA GROUND CONTROL PADA UNIT AERODROME CONTROL TOWER DI PERUM LPPNPI CABANG DENPASAR - Niken Yulian Laraswati; Djoko Jatmoko (Langit Biru: Jurnal Ilmiah Aviasi, 2019)
This study aims to determine how the influence of the apron taxiway at I Gusti Ngurah Rai International Airport to the workload of ground control in the aerodrome control tower unit of Perum LPPNPI Denpasar Branch. The method used in this study is descriptive research with qualitative approach. Data collection techniques used are participatory observation, interviews, and documentation. In this study also used a questionnaire as supporting data to identify the workload of ground control. The data analysis technique used is gap analysis and in depth interviews followed by triangulation techniques to test the credibility of data. The conclusion of this study explain that current apron taxiway configuration has not been able to accommodate the existing traffic load because there are still many delays that occur due to the area being the point of conflict, so that it can increase the workload of ground control. With this result, to improve traffic flow in manoeuvring area and to reduce the workload of ground control, it is necessary to develop rapid exit taxiways that do not deal directly with parking stands and the establishment of clearance delivery units, thereby reducing the level of aircraft delays.